In situ neutron diffraction study of the formation of Ho2Ge2O7 pyrochlore at high temperature and pressure. Issue 44 (27th October 2017) - Playford, Helen Y.; Bull, Craig L.; Tucker, Matthew G.; Funnell, Nicholas P.; Ridley, Christopher J.; Marshall, Kenneth P.; Walton, Richard I.
Abstract : The formation of the spin-ice pyrochlore Ho2 Ge2 O7 by two different high temperature, high pressure routes has been explored using in situ neutron diffraction. Abstract : The formation of the spin-ice pyrochlore Ho2 Ge2 O7 by two different high temperature, high pressure routes has been explored using in situ neutron diffraction. The first route involves the solid-state reaction of Ho2 O3 and GeO2, and formation of the pyrochlore phase is observed at 994(27) °C and 3.81(2) GPa, which are significantly milder conditions than those previously reported. The second route involves the hydrothermal synthesis of the tetragonal Ho2 Ge2 O7 pyrogermanate from Ho(NO3 )3 ·5H2 O and GeO2 and its subsequent transformation to the pyrochlore phase, which is observed at 683(23) °C and 3.89(3) GPa. The lowering of the formation temperature of high pressure phases by employment of a precursor of appropriate stoichiometry may also have applications in the wider field of solid-state chemistry.